Effect of Online Education Model On Knowledge Regarding Sexual and Reproductive Health Among Pre-Marital Couples - Murni, Hasrah; Y, Darmayanti; Arneti, Arneti (Pelopor Publikasi Akademika, 2023)
ABSTRACT: Lack of knowledge about sexual and reproductive health is still a problem that needs to be addressed among premarital couples. The use of online education method can provide an effective option for increasing knowledge and awareness of how to maintain reproductive health and prevent the transmission of sexual diseases post-marriage. A quasi-experimental design with a comparison group was conducted from April to November 2019 at a Public Health Centers in Bukittinggi city, West Sumatra, Indonesia. The total participants were 30 in the intervention group and 30 in the comparison group. Pre-marital couple in the intervention group received a online education module that was developed by the researcher. On the other hand, participants in the comparison group received a regular handbook. Knowledge was assessed by using a modified Knowledge of reproductive and sexual health. Data were analysed using paired t-test and independent t-tests for the inferential statistic. This study found an online education method significantly increased participants’ knowledge in the intervention group (p = .002). In the comparison group, the regular handbook significantly also improved participants’ knowledge (p =.035). However, the change of pre-test and post-test mean score of participants’ knowledge in the intervention group was significantly higher than those in the comparison group. It can be concluded that the online education method with an effective module development was significantly improved knowledge of pre-marital couples. Public health care provider should regularly concern to improve the strategy to prevent the incidents of the transmission of sexual diseases post-marriage.